2018
DOI: 10.1007/s40264-018-0653-3
|View full text |Cite|
|
Sign up to set email alerts
|

Review of Case Narratives from Fatal Overdoses Associated with Injectable Naltrexone for Opioid Dependence

Abstract: Vivitrol adverse event reports suggest the need to investigate two months following the last medicine injection as a period of particular concern for overdose. A registry study would best quantify risk. Providers should report suspected post-discontinuation overdoses to government authorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Out of 263 potential overdose deaths identified, 52 cases had exposure to injectable naltrexone for opioid use disorder. Among those whose last naltrexone administration date was known (n=28), approximately 18% (n=5) were on treatment (i.e., within 28 days of the last injection), 61% (n=17) occurred after 28 days but before two months, and 21% (n=6) occurred later [9]. These hypothesis-generating data suggest that there may be a one -month post-treatment exposure window during which individuals are at high risk for opioid overdose.…”
mentioning
confidence: 99%
“…Out of 263 potential overdose deaths identified, 52 cases had exposure to injectable naltrexone for opioid use disorder. Among those whose last naltrexone administration date was known (n=28), approximately 18% (n=5) were on treatment (i.e., within 28 days of the last injection), 61% (n=17) occurred after 28 days but before two months, and 21% (n=6) occurred later [9]. These hypothesis-generating data suggest that there may be a one -month post-treatment exposure window during which individuals are at high risk for opioid overdose.…”
mentioning
confidence: 99%
“…Here, we raise concerns regarding the methodology used and conclusions reached in a recent publication by Saucier et al [ 1 ] that retrospectively evaluated cases of spontaneously reported opioid overdose in patients treated with extended-release injectable naltrexone (XR-NTX; VIVITROL ® ) using a US FDA dataset. We concentrate on some specific points, but other concerns include failure to cite published data related to longer-term use of XR-NTX [ 2 , 3 ], citations of media articles, and the funding of this study by a non-scientific advocacy organization [ 1 ].…”
mentioning
confidence: 99%
“…Post-marketing safety surveillance is a public health imperative, and Alkermes adheres to rigorous FDA standards regarding the collection, follow-up, and submission of spontaneous case reports for all marketed Alkermes products, including VIVITROL. The most recent Alkermes review of cumulative post-marketing safety data submitted to the FDA (April 2017) evaluated > 360,000 patients treated with XR-NTX and included the data evaluated by Saucier et al [ 1 ]. This review did not demonstrate an increased risk of opioid overdose, including fatal overdose, either on treatment with XR-NTX or within 2 months of discontinuation, as implied by Saucier et al [ 1 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations